EPISTEMOLOGI ILMU ASBAB AL-WURUD HADIS - Lestari, Lenni (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
Apple-interchange-newline"> This paper is supposed to explore the epistemology of sabab al-wurÅ«d of hadith. The fial result are: First, asbÄb al-wurÅ«d is defied as a knowledge which pay attention to the causes of the emergence of an hadith and the condition around it. Second, the source of asbÄb al-wurÅ«d knowledge are books (read: creation) which related to the knowledge of asbÄb al-wurÅ«d. Third, the method to get asbÄb al-wurÅ«d is mainly trough narration (riwayat) and effort on judgment (ijtihad). Both last methods are dividedinto two, that are trough the narration of micro asbÄb al-wurÅ«d andtrough the effort on judgment of macro asbÄb al-wurÅ«d. Every hadith hasmacro asbÄb al-wurÅ«d but not every one of it has micro asbÄb al-wurÅ«d.Fourth, asbÄb al-wurÅ«d, as a knowledge is a science focuses to the studyof matn. Fifth, historically, asbÄb al-wurÅ«d didnâ€™t have any contact to thephilosophy of science, but based on truth theory, the one which is moreappropriate to the process of asbÄb al-wurÅ«dâ€™s validation is the coherencetruth theory.